Impact of the Choice of Land Surface Scheme on a Simulated Heatwave Event: The Case of Sichuan-Chongqing Area, China - Y. Ma; X.-M. Zeng; Y. Zhang; N. Wang; Y. Zheng; G. Wang; C. Chen (Advances in Meteorology)
The Sichuan-Chongqing area in China has complex basin topography and is known for its extremely hot summer weather. In this paper, the mesoscale model WRF version 3.6.1 was used to simulate a period of 1–10 days in advance of the hot weather that occurred in Sichuan-Chongqing on August 10, 2006, to investigate the effect of six different land surface schemes (LSSs) (SLAB, RUC, PX, NOAH, NOAH_MP, and CLM4) on short- and medium-range simulations of high temperatures. The simulated surface air temperatures (SATs) are sensitive to the LSSs and simulation lengths. Specifically, all of the LSSs except PX generally reproduce the observed high temperatures, with CLM4 SATs at 06 UTC (SAT06) the most consistent with measurements whereas the short-range (medium-range) results from NOAH_MP (NOAH) are the worst. Detailed explanations were given in terms of surface fluxes and physical processes. RUC soil moisture initialization appears poor and the LSS reflects too strong gravity drainage. When the LSSs with increased numbers of soil layers are used, the simulated high temperatures are found more consistent with measurements. Additionally, regional sensible heat flux (SHF) does not show high consistency with SAT. The results that differ from the previous studies are partly due to the complex geography and the LSS deficiencies.